Renewable energies evaluation and linking to smart grid - Benouaz Idriss Yassine; Allaoua Boumediene (Institute of Advanced Engineering and Science, 2020)
To tackle the widespread challenges encountered during the management of power flow in electrical networks, the integration of smart grid (S.G)is proposed as a viable solution to address the environmental and economic concerns. In order to enhance overall functionality of the electric power delivery system, operation of the smart grid is governed by data-driven algorithms where various sensors and smart meters are used to collect this data. On other hand, the fluctuating cost of fossil fuels and its negative impact on the environment has incentivized the exploitation of renewable energies in the smart grid. In the present paper, a hybrid Photovoltaic/Wind (PV/Wind) is suggested to supply a smart grid. The objective of this study is to asses the feasibility of a smart grid supplied solely by renewable energy sources. Conceptual standings of this newly suggested model are validated by simulations.